The influence of leader-member exchange and organizational climate on military organizational commitment - Adya Hermawati; Hartini Prasetyaning Pawestri; Kartika Dewi Sri Susilowati; Martaleni Martaleni; Roby Sambung (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2021)
This study aims to determine the effect of leader-member exchange and organizational climate on organizational commitment mediated by work performance. This study is explanatory research, and the sample analysis of this research is the military personnel of the 30th maintenance department, Abdul Rachman Saleh Malang Airbase. In this study, the researchers set a sample size of 100 respondents and tested the research’s model by the Partial Least Square approach. This study shows that organizational climate can directly encourage organizational commitment while leader-member exchange has a positive effect when mediated by work performance.